Bacterial translocation in cirrhotic rats. Its role in the development of spontaneous bacterial peritonitis. Issue 11 (November 1994) - Llovet, J M; Bartolí, R; Planas, R; Cabré, E; Jimenez, M; Urban, A; Ojanguren, I; Arnal, J; Gassull, M A
Abstract : Bacterial translocation occurs in ascitic cirrhotic rats, but its association with ascites infection is unknown. The aim of this study was to assess the relation between bacterial translocation and ascites infection in cirrhotic rats. Male Sprague-Dawley rats were induced to cirrhosis with intragastric CCl4. Ascitic fluid, portal and peripheral blood, mesenteric lymph nodes, liver and spleen samples were cultured before death in those cirrhotic rats with less (group A) or more (group B) than 250 polymorphonuclear neutrophils/mm3 in ascitic fluid, as well as in healthy control rats. Histological examination of jejunum, ileum, and caecum was also performed. Bacterial translocation occurred in 45% of ascitic rats (without differences between groups A and B), but in 0% controls (p = 0.01). Bacterial translocation was associated with positive ascitic fluid culture in 60% of the cases. In all of them the same bacterial species was isolated in both mesenteric lymph node and ascitic fluid. Submucosal caecal oedema (100%), ileal lymphangiectasia (41%), and caecal inflammatory infiltrate (41%) occurred in ascitic rats, the last being associated with ascitic fluid positive culture (p = 0.04). These results suggests that bacterial translocation occurs frequently in ascitic cirrhotic rats, and may play a permissive, but not unique, part in a number of ascites infections. Whether histological changes seen in cirrhotic ascitic rats favour bacterial translocation remains to be elucidated.